2014
DOI: 10.1016/j.egypro.2014.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Seawater-proof Hybrid Photovoltaic/thermal (PV/T) Solar Collector

Abstract: Hybrid photovoltaic/thermal (PV/T) systems provide both electrical and thermal energy. The development of seawater-proof PV/T systems can enlarge the, by now, very limited PV/T application fields to a new one: sustainable reverse osmosis (RO) desalination. There, the PV/T systems' disadvantage of heat at low temperature level can redound to its advantage: the RO freshwater output is increased at elevated seawater temperatures while the PV efficiency is improved due to cooling with seawater. In this paper, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…At this point it should be noted that except of PVT applications for buildings (e.g. for domestic water heating: [2]), PVT systems also provide other types of applications such as desalination [12] and drying of agricultural products [13].…”
Section: Symbols / Abbreviationsmentioning
confidence: 99%
“…At this point it should be noted that except of PVT applications for buildings (e.g. for domestic water heating: [2]), PVT systems also provide other types of applications such as desalination [12] and drying of agricultural products [13].…”
Section: Symbols / Abbreviationsmentioning
confidence: 99%
“…Fig. 30 shows the integration of a thermal absorber with the PV layer by the fixing of rods with springs [31]. The polypropylene absorber is pressed against the back of the PV module by a construction consisting of five aluminium rods, springs, and aluminium strips.…”
Section: Mechanical Fixingmentioning
confidence: 99%
“…It is feasible to make further use of the absorbed heat through a heat pump for one or more of the following purposes, i.e. hot water supply [23][24][25], space heating [26,27], solar cooling [28,29], thermal storage [30], desalination [31], drying [32,33] and pool heating [34,35] etc. Electricity generation from the PV cells, either exported to the national grid or stored in batteries, will meet the electrical load or drive the system component, i.e.…”
Section: Flat-plate Pv/t Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature widely discussed works on the application of photovoltaic-thermal (PVT) solar systems with a low-temperature heat carrier [2], in which the solar cells are placed on a flat cooled walls of different geometry and are protected by thermal glass. The authors of [3] went around this drawback by using a low-temperature heat carrier capacity of the heat exchanger to preheat the salt water in the solar distillers, with the result that increase the productivity of fresh water produce at ≈ 30%. In [4] it is shown that with the use of PVT collector with aluminum reflectors mounted on both sides solar radiation intensity increases from ≈ 43% to ≈ 65%, generates electric power 17% higher, and the heat by 55% higher compared with PVT collectors without concentration.…”
Section: Introductionmentioning
confidence: 99%